Identification of bioactive compounds with GC–Q-TOF–MS in the extracts from clinacanthus nutans using subcritical carbon dioxide extraction - Alam, Md. Ariful; Sarker, Md. Zaidul Islam; Ghafoor, Kashif; Ferdosh, Sahena; Asing, Md. Eaqub Ali; Mirhosseini, Hamed; Yunus, Kamaruzzaman; Jahurul, Md. Haque Akanda; Khatib, Alfi (Taylor & Francis, 2017)
Subcritical carbon dioxide Soxhlet extraction of biologically active compounds from Clincanthus nutans was investigated by full factorial design to identify and optimize the factors (particle size and co-solvent) affecting extract yield, antioxidant activity, total phenolic content, total flavonoid content, and α-glucosidase inhibitory activity. An average of 3.103% yield, 98.90% antioxidant activity, 49.40 mg/g (GAE) TPC, 43.76 mg/g (RE), and 88.58% AGI activity can be achieved using the optimum levels of independent variables. The GC Q-TOF MS identification of optimized extract shown that different classes of phytoconstituents were successfully separated by CO2-Soxhlet to produce potential antioxidant and α-glucosidase inhibitory activity.